Expanded gold standard in the diagnosis of Chlamydia trachomatis in a low prevalence population: diagnostic efficacy of tissue culture, direct immunofluorescence, enzyme immunoassay, PCR and serology. Issue 5 (October 1994) - Thejls, H; Gnarpe, J; Gnarpe, H; Larsson, P G; Platz-Christensen, J J; Ostergaard, L; Victor, A
Abstract : OBJECTIVE–To evaluate the diagnostic efficacy of chlamydia culture, direct immunofluorescence (DFA), direct enzyme immunoassay (EIA), polymerase chain reaction (PCR) and serology by defining positive culture or at least two positive non-culture tests as true positive. SETTING–Three gynaecological departments located in separate areas of Sweden. PATIENTS AND DESIGN–All pregnant women requesting abortion during a six month period were included. In cases with unconfirmed non-culture tests, reculture with multiple passage and PCR on the culture transport medium was performed for confirmation. Serum was analysed for chlamydial antibodies type IgG, IgM and IgA using microimmunofluorescence. RESULTS–18 of 419 (4.3%) patients were positive for chlamydia according to the defined criteria. Twelve of 419 (2.9%) were positive in standard culture (primary inoculation). The sensitivity of standard culture, DFA, EIA and PCR were 66.7%, 77.8%, 64.7% and 71.4% respectively. The specificity 100% (by definition), 99.5%, 100%, 100% respectively. The positive predictive value 100% (by definition), 87.5%, 100%, 100% respectively. Negative predictive value 98.5%, 99.0%, 98.5%, 98.9% respectively. Serum IgG titre of > or = 64 and > or = 1024 gave positive predictive values of 10% and 21% respectively. CONCLUSIONS–When an expanded gold standard is used, the specificity and positive predictive value of the non-culture tests used are comparable with that of standard culture even in this low prevalence population. Standard culture underestimated the chlamydia prevalence by 33%. The prevalence found represents a decrease from 10 to 2.9% of culture verified chlamydia during four years in comparable populations. Chlamydial antibodies of certain immunological classes are not necessarily present in cases with chlamydia.